Pengaruh Jenis Mulsa terhadap Pertumbuhan dan Hasil Tiga Kultivar Kentang (Solanum tuberosum L.) yang Ditanam di Dataran Medium - Jajang Sauman Hamdani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The objectives  of  the  experiment  were to study  growth and yield of three potato (Solanum tuberosum L.)  cultivars   planted at medium altitude with different  types of mulch. The experiment is located  at experimental  station of Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang at an altitude of about 680 m.  The experiment was arranged in a Randomized Completed Block Design with factorial pattern, consisting of two factors and three replications.  First factor was potato cultivar (Granola, Kennebec, and Panda), and the  second factor was types of mulch, consisted of three levels : without mulch, straw mulch, and silver black polyethylene mulch. The result of the experiment showed that Panda cultivar had highest dry weight (29.5 g/plant) and leaf area (2513.7 cm2), while Granola  cultivar had  highest number of tuber  per plant  (15.17 knol/plant ) and highest tuber weight per plant was  650.6 g/plant (30.3  t.ha-1). Straw and silver black polyethylene mulches increased leaf area, dry weight, number of tuber per plant and tuber weight per plant. The effect of  interaction betwen potato cultivar and source of mulch was significant on plant height.  Panda cultivar and silver black polyethylene mulch resulted the highest height of plant (68.2 cm).      Key words:  Potato cultivar, mulch, medium altitude